Impact of Textile Effluents on Pistia stratiotes L. and Ludwigia adscendens L. Using Hydroponic Culture - Momtaz, Halima; Alam, AKM Rashidul; Islam, M Shahidul; Haque, Sirajul (Bangladesh Journal of Scientific and Industrial Research, 2010)
The study was carried out to assess the impacts of textile effluents on aquatic plants by using hydroponic culture. Effluent water of three textile industries and effluent free water were collected from Savar region. The higher contents of pH (10.47), total suspended solids (1407.33 mg/L), total dissolved solids (19014 mg/L) and biochemical oxygen demand (735 mg/L) were recorded in industrial effluents comparing with control. The lowest content of DO in industrial effluents (0.87 mg/L) was much lower than the control (5.65 mg/L). Hydroponic test showed that 100, 75, 50, 25 and 1% textile effluents caused the death of Pistia stratiotes L. and Ludwigia adscendens L. within 1-4, 2- 6, 3-9, 5-12 and 14-17 days, respectively. When P. stratiotes was grown in 100% effluent water its concentrations of Cr, Cd, Cu, Mn, Ni and Zn were 8.00, 1.4375, 189.06, 1843.1, 5.075 and 261.87 ppm, respectively and the test species died within 1 - 3 days. When L. adscendens was grown in 100% effluent water, its concentrations of Cr, Cd, Cu, Mn, Ni and Zn were 7.25, 0.975, 312.87, 1621.2, 5.0125 and 138.75 ppm, respectively and the test species died within 2-4 days. The uptake of heavy metals increased with raising effluent concentration comparing with control culture. The uptake of Cr, Cd, Cu, Mn, Ni and Zn were significantly higher at 50%, 75% and 100% (p = 0.01** at 1% level of significance) effluent which caused the death of both test species. Key words: Textile effluents; Pistia stratiotes L.; Ludwigia adscendens L.; Hydroponic culture. DOI: 10.3329/bjsir.v45i1.5172 Bangladesh J. Sci. Ind. Res. 45(1), 9-16, 2010